2012
DOI: 10.1161/circheartfailure.111.963314
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled NO and Sildenafil Combination in Cardiac Surgery Patients With Out-of-Proportion Pulmonary Hypertension

Abstract: Background-The goal of this study was to examine the effects of coadministration of sildenafil and inhaled nitric oxide (iNO) in patients with out-of-proportion pulmonary hypertension who underwent cardiac valve replacement surgery. Methods and Results-Twenty consecutive cardiac surgery patients with out-of-proportion pulmonary hypertension were randomly assigned postoperatively into 2 groups: group A received 10 ppm of iNO followed by sildenafil (100 mg) orally 30 minutes later, and group B initially received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…In these pulmonary hypertensive animals, we have previously shown that PVR is elevated (7,18) and PDE5 activity is increased (18). Yet, there is animal (27) and clinical (12) evidence that the sildenafil and inhaled NO combination results in greater pulmonary vasodilation compared with the use of either agent individually. Sildenafil has been recently shown to have a positive inotropic effect on cardiomyocytes (24), possibly explaining its additive therapeutic beneficial effect independent from its pulmonary vasodilator activity.…”
Section: Discussionmentioning
confidence: 95%
“…In these pulmonary hypertensive animals, we have previously shown that PVR is elevated (7,18) and PDE5 activity is increased (18). Yet, there is animal (27) and clinical (12) evidence that the sildenafil and inhaled NO combination results in greater pulmonary vasodilation compared with the use of either agent individually. Sildenafil has been recently shown to have a positive inotropic effect on cardiomyocytes (24), possibly explaining its additive therapeutic beneficial effect independent from its pulmonary vasodilator activity.…”
Section: Discussionmentioning
confidence: 95%
“…These continue to demonstrate biological benefits, hemodynamically important physiological benefit and have begun to demonstrate some meaningful clinical outcomes such as reduction in duration of mechanical ventilation and stay in the intensive care unit (74)(75)(76)(77)(78)(79)(80). However, these studies remain to involve only a limited surgical patient population, have not progressed beyond single institutional boundaries and lack any demonstration of survival benefit.…”
Section: C the Last Decade Of Ino Therapy In Routine Cardiac Surgerymentioning
confidence: 99%
“…W przypadku chorych po transplantacji serca leczenie inhalacjami NO indukowało selektywne zmniejszenie PVR bez wpływu na opór systemowy [32]. W nowszych badaniach stwierdzono, że łączne zastosowanie w okresie pooperacyjnym u chorych z PH po operacjach kardiochirurgicznych inhalacji NO i doustnego podawania sildenafilu było bezpieczne i wiązało się z obniżeniem PAP i PVR bez systemowej hipotonii i zaburzeń stosunku wentylacji do perfuzji [33].…”
Section: Leczenie I Kierunki Rozwojuunclassified